Prevalence of Significant Tricuspid Regurgitation in Patients Planned for Mitral Valve Surgery in a Tertiary Center of Nepal - Sharma Parajuli, S.; Rajbhandari, N.; Panthee, N.; Timshina, A. (Kathmandu University Medical Journal, 2022)
Background Tricuspid regurgitation is frequently present in patients with mitral valve disease and most of this tricuspid regurgitation present are significant. Objective To find out the prevalence of tricuspid regurgitation in adult patients present in our hospital who are planned for isolated mitral valve surgery for mitral stenosis, mitral regurgitation or both. Patients with moderate and severe tricuspid regurgitation were considered as significant. Method This was the retrospective cross-sectional study performed at Shahid Gangalal National Heart Center of Nepal. All cardiac surgical patients scheduled for isolated mitral valve surgery during the 3 years’ period from 2017 to 2020 were enrolled in the study and presence or absence of significant tricuspid regurgitation were recorded and analysed. Result Out of total patients 65% (663) of the cases with mitral valve pathology had significant tricuspid regurgitation. Out of the total mitral stenosis cases 70% were associated with significant tricuspid regurgitation, 62.6% of the cases of mitral regurgitation had significant tricuspid regurgitation and 64.8% of patients with combined mitral stenosis and regurgitation were associated with significant tricuspid regurgitation. Conclusion Significant tricuspid regurgitation is present in most of the cases with isolated mitral valve pathology. So routine tricuspid valve evaluation and repair if needed during mitral valve surgeries is recommended.